China's Energy Strategy and Cooperation with Kazakhstan (International relations and international law Journal, 2016)
The article discusses the evolution of China's energy strategy development, formation and development of China 's oil industry, as well as a connection between the social development of China's economy and energy demand. China's transition from the energy strategy of " taking care of yourself » ("the Energy Self – sufficiency") to the " oil supply and care of yourself» ("the Energy Supply – oriented"), China discovered the danger of oil imports through sea route, they became interested in energy relations with Kazakhstan, established energy cooperation between China and Kazakhstan,as well as bilateral cooperation and the need of its regularity was proved.
Keywords: China; energy; strategy; "taking care of yourself»; oil supply and care of yourself »; Kazakhstan; cooperation; development